Training and development and employees’ performance: A study based on state banks in Jaffna - Sumangala, P.; Raveendran, T. (University of Jaffna, 2020)
The present study aims to identify the impact of Training and Development on employees’ performance in state Banks in Jaffna. Training and development were analyzed based on three variables: knowledge, skill and attitude and employees’ performance were measured based on quality of the work, handling the problems, positive behavior of employees, and teamwork. The state banks covered in the study include Bank of Ceylon, People’s Bank and National Savings Bank. 107 employees participated in the study and a simple random sampling method was used to select the samples. Data were collected using questionnaires. The study's findings show that Training and Development have a a positive Impact on employees’ performance in State Banks in Jaffna. Further, it was found that the number of training attended does not moderate the impact of Training and development on employees’ performance. Findings of the study will help top management plan the training and development activities efficiently in the future
Keywords: banking sector; employee performance; training and development